Reconstruction of three centuries of annual accumulation rates based on the record of stable isotopes of water from Lomonosovfonna, Svalbard - Pohjola, V.; Martma, T.; Meijer, H.A.J.; Moore, J.; Isaksson, E.; Vaikmae, R.; van de Wal, R.S.W. (Annals of Glaciology, 2002)
We use the upper 81 in of the record of stable isotopes of water from a 122 in long ice core from Lomonosovfonna, central Spitsbergen, Svalbard, to construct an ice-core chronology and the annual accumulation rates over the icefield. The isotope cycles are counted in the ice-core record using a model that neglects short-wavelength and low-amplitude cycles. We find approximately the same number of delta(18)O cycles as years between known reference horizons, and assume these cycles represent annual cycles. Testing the validity of this assumption using cycles in deltaD shows that both records give similar numbers of cycles. Using the delta(18)O chronology, and decompressing the accumulation records using the Nye flow model, we calculate the annual accumulation for the ice-core site back to AD 1715. We find that the average accumulation rate from 1715 to 1950 was on average 0.30 in w.e. Accumulation rates increased about 25% during the later part of the 20th century to an average of 0.41 in w.e. for the period 1950-97. The accumulation rates show highly significant 2.1 and 21 year periodicities, which gives credibility to our time-scale.